Influence of Varying Dietary ω6 to ω3 Fatty Acid Ratios on the Hepatic Transcriptome, and Association with Phenotypic Traits (Growth, Somatic Indices, and Tissue Lipid Composition), in Atlantic Salmon (Salmo salar) - Tomer Katan; Xi Xue; Albert Caballero-Solares; Richard G. Taylor; Christopher C. Parrish; Matthew L. Rise (Biology, 2021)
The importance of dietary omega-6 to omega-3 (ω6:ω3) fatty acid (FA) ratios for human health has been extensively examined. However, its impact on fish physiology, and the underlying molecular mechanisms, are less well understood. This study investigated the influence of plant-based diets (12-week exposure) with varying ω6:ω3 (0.4–2.7) on the hepatic transcriptome of Atlantic salmon. Using 44 K microarray analysis, genes involved in immune and inflammatory response (lect2a, itgb5, helz2a, p43), lipid metabolism (helz2a), cell proliferation (htra1b), control of muscle and neuronal development (mef2d) and translation (eif2a, eif4b1, p43) were identified; these were differentially expressed between the two extreme ω6:ω3 dietary treatments (high ω6 vs. high ω3) at week 12. Eight out of 10 microarray-identified transcripts showed an agreement in the direction of expression fold-change between the microarray and qPCR studies. The PPARα activation-related transcript helz2a was confirmed by qPCR to be down-regulated by high ω6 diet compared with high ω3 diet. The transcript expression of two helz2 paralogues was positively correlated with ω3, and negatively with ω6 FA in both liver and muscle, thus indicating their potential as biomarkers of tissue ω6:ω3 variation. Mef2d expression in liver was suppressed in the high ω6 compared to the balanced diet (ω6:ω3 of 2.7 and 0.9, respectively) fed fish, and showed negative correlations with ω6:ω3 in both tissues. The hepatic expression of two lect2 paralogues was negatively correlated with viscerosomatic index, while htra1b correlated negatively with salmon weight gain and condition factor. Finally, p43 and eif2a were positively correlated with liver Σω3, while these transcripts and eif4b2 showed negative correlations with 18:2ω6 in the liver. This suggested that some aspects of protein synthesis were influenced by dietary ω6:ω3. In summary, this nutrigenomic study identified hepatic transcripts responsive to dietary variation in ω6:ω3, and relationships of transcript ...